Expression of human CD46 and trans-complementation by murine adenovirus 1 fails to allow productive infection by a group B oncolytic adenovirus in murine cancer cells. Issue 1 (13th June 2018) - Lei, Janet; Jacobus, Egon J.; Taverner, William K.; Fisher, Kerry D.; Hemmi, Silvio; West, Katy; Slater, Lorna; Lilley, Fred; Brown, Alice; Champion, Brian; Duffy, Margaret R.; Seymour, Len W.
Abstract : Background: Oncolytic viruses are currently experiencing accelerated development in several laboratories worldwide, with some forty-seven clinical trials currently recruiting. Many oncolytic viruses combine targeted cytotoxicity to cancer cells with a proinflammatory cell lysis. Due to their additional potential to express immunomodulatory transgenes, they are also often known as oncolytic viral vaccines. However, several types of oncolytic viruses are human-specific and the lack of suitable immune-competent animal models complicates biologically relevant evaluation of their vaccine potential. This is a particular challenge for group B adenoviruses, which fail to infect even those immunocompetent animal model systems identified as semi-permissive for type 5 adenovirus. Here, we aim to develop a murine cell line capable of supporting replication of a group B oncolytic adenovirus, enadenotucirev (EnAd), for incorporation into a syngeneic immunocompetent animal model to explore the oncolytic vaccine potential of group B oncolytic viruses. Methods: Transgenic murine cell lines were infected with EnAd expressing GFP transgene under replication-independent or -dependent promoters. Virus mRNA expression, genome replication, and late protein expression were determined by qRT-PCR, qPCR, and immunoblotting, respectively. We also use Balb/c immune-competent mice to determine the tumourogenicity and infectivity of transgenic murine cell lines. Results: Our results show that a broad range of human carcinoma cells will support EnAd replication, but not murine carcinoma cells. Murine cells can be readily modified to express surface human CD46, one of the receptors for group B adenoviruses, allowing receptor-mediated uptake of EnAd particles into the murine cells and expression of CMV promoter-driven transgenes. Although the early E1A mRNA was expressed in murine cells at levels similar to human cells, adenovirus E2B and Fibre mRNA expression levels were hampered and few virus genomes were produced. Unlike previous reports on group C adenoviruses, trans-complementation of group B adenoviruses by co-infection with mouse adenovirus 1 did not rescue replication. A panel of group B adenoviruses expressing individual mouse adenovirus 1 genes were also unable to rescue EnAd replication. Conclusion: Together, these results indicate that there may be major differences in the early stages of replication of group C and B adenoviruses in murine cells, and that the block to the life cycle of B adenoviruses in murine cells occurs in the early stage of virus replication, perhaps reflecting poor activity of Ad11p E1A in murine cells.